Nocardia brasiliensis Preseptal Cellulitis in an Immunocompetent Patient. Issue 1 (January 2019) - Kareff, Samuel; Gottlieb, Lindsey; Maturana, Colleen; Caplivski, Daniel
Abstract : Abstract: The Nocardia subspecies are opportunistic pathogens ubiquitous in the environment that most often cause infection in immunocompromised hosts. Here we describe a case of community-acquired preseptal cellulitis in a previously healthy man who we believe acquired the infection from contact with soil while gardening.